(untitled) (Global Journal of Science Frontier Research, 2025)
The fundamental place in the development of civilization is occupied by the production of goods from minerals in the bowels of the Earth and it is growing faster than the number of people These two factors despite the lack of alternatives in their essence create problems due to the negative impact on natural systems that must be eliminated Firstly the resources in the continental crust can be exhausted within 50-200 years Secondly natural ecosystems are degrading and are irreversibly destroyed The good intentions of society are fulfilled by destroying the natural balance and worsening the comfortable conditions of equilibrium created by nature both in the used subsoil massif itself and in the surrounding near-ore space and on the surface